Analysis of rectangular thin plates and plate structures basing on the Vlasov's variational procedure1 - Altenbach, Johannes; Naumenko, Konstantin; Naumenko, Vladimir K. (Computer Assisted Methods in Engineering and Science, 2023)
The solution procedure proposed by Vlasov based on the reduction of the basic two-dimensional boundary value problems into ordinary differential equations provides a good accuracy in the case of rectangular domains with small size ratios. The paper presents an extension of this method applied to rectangularKirchhoff's plates in connection with the iterational scheme. The results are compared with analytical solutions available for rectangular plates with simplified boundary conditions and loading. The possibilities of application of the solutions for simple plate geometry to complex plate problems (e.g. complex geometry, boundary conditions) are discussed and illustrated by numerical examples.